KEJADIAN AFASIA PADA STROKE FASE AKUT DAN PERUBAHAN SINDROM AFASIA PASCASTROKE - Vania Angeline Bachtiar; Paulus Anam Ong; Sobaryati Sobaryati; Uni Gamayani; Lisda Amalia; Siti Aminah (PERDOSNI, 2018)
THE OCCURRENCE AND EVOLUTION OF APHASIA SYNDROME WITHIN ONE MONTH AFTER STROKEABSTRACTIntroduction: Aphasia is a barrier for the rehabilitation of patients with stroke. The examination of aphasia is not only for diagnostic purpose, but also for the patient remaining language proficiency information and for comprehensive stroke treatment.Aims: To study the incidence rate of aphasia in acute ischemic stroke and the change of the aphasia syndrome one month after stroke.Methods: A descriptive observational with cohort study on ischemic stroke patients in Neurology ward, Dr. Hasan Sadikin Hospital and other hospitals in Bandung between November 2017 and February 2018. Tes Afasia, Diagnosis, Informasi dan Rehabilitasi(TADIR, a tools for diagnostic and rehabilitation of aphasia for Indonesian) was used to diagnose aphasia initially and repeated one month after diagnosis.Results: Aphasia was found in 24 out of 102 patients with acute ischemic stroke (23.5%). Majority was male (58.3%), the average age of the patients was 55.6±11,4 years and 8.8 years of education. The most common type of stroke causing aphasia was cardioembolic (62.5%). Based on the types, the most aphasia syndrome found in this study were global aphasia (58.3%), followed by Broca aphasia (25%). Twenty patients with aphasia were re-examined after one month and 40% patients experienced transformation into other type of aphasia syndrome. Between patients with global aphasia, 45.5% transformed into Broca aphasia and 9% into transcortical motor aphasia. Patients with Broca aphasia did not experience transformation, 50.0% of Wernicke aphasia transformed into conductive aphasia, and one conductive aphasia patient transformed into anomic aphasia.Discussion: The occurrence of aphasia in acute ischemic stroke is 23.5%. Within one month after stroke, 40% patients with aphasia have shown transformation from one type into other type of aphasia syndrome.Keyword: Aphasia, language proficiency, stroke, TADIRABSTRAKPendahuluan: Afasia dapat menghambat rehabilitasi pasien stroke. Pemeriksaan afasia, tidak hanya untuk keperluan diagnosis, namun juga sebagai informasi kemampuan berbahasa pasien yang tersisa dan akan bermanfaat untuk tata laksana stroke yang komprehensif.Tujuan: Mengetahui kejadian afasia pada stroke iskemik fase akut dan perubahannya pada satu bulan kemudian.Metode: Penelitian deskriptif observasional dengan rancangan kohort terhadap pasien stroke iskemik yang dirawat di ruang rawat inap Neurologi RSUP Dr. Hasan Sadikin dan beberapa RS di Bandung dan sekitarnya pada bulan November 2017 sampai Februari 2018. Penilaian afasia menggunakan Tes Afasia, Diagnosis, Informasi, dan Rehabilitasi (TADIR) yang diulang pada satu bulan kemudian.Hasil: Afasia ditemukan pada 24 dari 102 pasien stroke iskemik fase akut (23,5%). Mayoritas subjek adalah laki-laki (58,3%) dengan rerata usia 55,6±11,4 tahun dan rerata lama pendidikan 8,8 tahun. Penyebab afasia terbanyak adalah stroke kardioemboli (62,5%). Sindrom afasia yang terbanyak ditemukan adalah afasia global (58,3%) diikuti afasia Broca (25%). Pemeriksaan ulang pada satu bulan pascastroke dilakukan terhadap 20 pasien afasia, dan didapatkan 40% mengalami perubahan sindrom. Sebanyak 45,5% pasien afasia global berubah sindrom menjadi afasia Broca dan 9,0% menjadi afasia transkortikal motorik. Afasia Broca tidak mengalami perubahan sindrom. Seorang pasien dengan sindrom afasia Wernike berubah menjadi afasia konduksi; dan satu pasien dengan sindrom afasia konduksi berubah menjadi afasia anomik.Diskusi: Kejadian afasia pada stroke iskemik fase akut adalah 23,5%. Satu bulan pascastroke, 40% pasien afasia mengalami perubahan sindrom.Kata kunci: Afasia, kemampuan berbahasa, stroke, TADIR